The effectiveness of using flip word games to improve students' vocabulary mastery - Prabowo, Aldi; Munawir, Ahmad; Amrang; Shaheen, Mohamed (Mell Baou Publisher, 2024)
This study aimed to examine the impact of the Flip Words Game on English vocabulary mastery among eighth-grade students at SMP Negeri 1 Wonomulyo using a quasi-experimental design. The sample included 60 students, divided into a control group (conventional methods) and an experimental group (Flip Words Game), each comprising 30 students. Both groups participated in four 40-minute sessions, and vocabulary mastery was assessed through pre- and post-tests. Data analysis using an independent sample t-test revealed a significant improvement in vocabulary mastery for the experimental group (t = 0.008, p < 0.05), with an N-Gain score in the medium category (0.5) compared to the control group’s low category (0.1). These results indicate that the Flip Words Game significantly enhances students' vocabulary mastery, supporting the hypothesis that this interactive method is effective for English language learning.